2021
DOI: 10.1016/j.abrep.2021.100369
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of exercise addiction in aerobic and anaerobic exercises: Beyond the components model of addiction

Abstract: Highlights The risk of exercise addiction (REA) is not different in aerobic and anaerobic exercise. Exercisers at REA report more additional symptoms than asymptomatic individuals. Women performing anaerobic exercise report eating more disorderly than men when exercise is not possible. The components model of exercise addiction should be expanded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Indeed, although a review suggested that there may be gender differences in exercise addiction (Dumitru et al, 2018), another review published in the same period revealed no sex differences (Nogueira et al, 2018). In this context, other studies suggest that if scholars consider a minimum exercise volume, there are no differences between the sexes (e.g., Pálfi et al., 2021). Finally, at least one early study disclosed higher exercise addiction in women than men (Pierce et al, 1997).…”
Section: Question No 7: Is There a Cultural Difference In Exercise Ad...mentioning
confidence: 99%
“…Indeed, although a review suggested that there may be gender differences in exercise addiction (Dumitru et al, 2018), another review published in the same period revealed no sex differences (Nogueira et al, 2018). In this context, other studies suggest that if scholars consider a minimum exercise volume, there are no differences between the sexes (e.g., Pálfi et al., 2021). Finally, at least one early study disclosed higher exercise addiction in women than men (Pierce et al, 1997).…”
Section: Question No 7: Is There a Cultural Difference In Exercise Ad...mentioning
confidence: 99%
“…Some authors have argued that although regular physical exercise is beneficial for both physical and mental health (Chang et al, 2019;Chekroud et al, 2018), when exercise becomes excessive or compulsive it can have detrimental effects on people's health, such as causing physical injuries or leading to the neglect of other important areas of their lives (Berczik et al, 2012;Morgan, 1979). Although a 'diagnosis' of compulsive exercising is not currently cited in any officially recognized medical or psychological diagnostic manual, there is consensus (Berczik et al, 2012;Chen, 2016;Pálfi et al, 2021;Szabo, 2010) that excessive exercise is a behavioral process that can provide pleasure or relief from internal discomfort and is characterized by repeated failure to control the behavior and maintenance of the behavior in spite of negative consequences (Goodman, 1990). Compulsive exercising also presents peculiar features such as exercising against medical advice or despite feeling unwell (Berczik et al, 2012;Lichtenstein & Jensen, 2016), missing social obligations because of exercise (Juwono & Szabo, 2020), and distorted perception of the volume of exercise (Pálfi et al, 2021).…”
Section: Compulsive Exercisementioning
confidence: 99%
“…Although a 'diagnosis' of compulsive exercising is not currently cited in any officially recognized medical or psychological diagnostic manual, there is consensus (Berczik et al, 2012;Chen, 2016;Pálfi et al, 2021;Szabo, 2010) that excessive exercise is a behavioral process that can provide pleasure or relief from internal discomfort and is characterized by repeated failure to control the behavior and maintenance of the behavior in spite of negative consequences (Goodman, 1990). Compulsive exercising also presents peculiar features such as exercising against medical advice or despite feeling unwell (Berczik et al, 2012;Lichtenstein & Jensen, 2016), missing social obligations because of exercise (Juwono & Szabo, 2020), and distorted perception of the volume of exercise (Pálfi et al, 2021).…”
Section: Compulsive Exercisementioning
confidence: 99%
“…Finally, a survey of 176 people who performed aerobic and anaerobic exercises at least three times a week found no difference between aerobic and non-aerobic exercisers in the EA or additional symptoms (Pálfi et al. 2021 ). However, these findings are only sporadic and unrelated.…”
Section: Introductionmentioning
confidence: 99%